Evaluation of the Analgesic Efficacy of two Doses of Oral Ibuprofen in Patients Presenting to the Emergency Department Complaining of Severe Pain - Muhammad Saqib Habib, Saqib Khalil, Abdul Azeem, Sameer Ahmed, Amanat Ali, Fayaz Ahmed Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to examine the relative effectiveness of two different oral dosages of ibuprofen in relieving pain in patients presenting to the emergency department complaining of sudden, severe discomfort. Study Design: Randomized, Double-blind trial Place and Duration: Islamic International Medical College and Trust Islamabad, during from January 2021 to June 2021. Methods: Total 180 patients of both genders with ages 20-75 years had acute pain were presented. After obtaining participants' informed consent, demographic data such as age, sex, BMI, and residence were collected from those who participated. Causes of pain among all cases were also recorded. Single doze 400mg was given to 90 patients in group I and doze of 800mg was given to group II. Visual analogue scale was used for measurement of pain score among both groups. SPSS 22.0 was used to analyze all data. Results: There were majority males 112 (62.2%) and 68 (37.8%) females in this study. Among 180 patients, 80 (44.4%) had age 21-30 years, 60 (33.3%) had age 31-40 years and 50 (27.8%) had age >40 years. Majority was from urban areas 105 (58.3%). Most common cause of acute pain was fallen, RTA, sports and knife abuse among all cases. We found no any significant difference in pain score at 2, 4 and 6 hours among both groups and both doses were effective among all cases in reduction of pain with p value <0.005. Post-treatment side effects were dizziness, nausea and diarrhea among both groups but there was also no any significant difference observed. Conclusion: We concluded in this study the oral ibuprofen (400mg, 800mg) was an effective and useful in reduction of pain score among patients admitted to ED because of injury. No any significant difference was observed between efficacy and as well as in side effects. Keywords: Acute Pain, ED, VAS, Ibuprofen, Side Effects